Causes of student failure in the economic-administrative areas at the Autonomous University of Sinaloa - Moreno López, Esteban Otoniel (Technium Education and Humanities, 2024)
The aim of this paper was to understand the phenomenon of failure, as a diagnosis, considering the scientific, social, and academic condition of the research. The dimensions and links of educational theories in their different variables such as teaching-learning that are related to teaching practices are also considered. Qualitative methods and techniques were used with students of the economic-administrative area of the Autonomous University of Sinaloa. Nowadays, for any society, the performance, and good results of the national education system, including higher education, are of vital importance. For this reason, it is necessary to carry out studies related to the factors that affect the failure rate, since it is necessary to strengthen the information systems to develop an adequate strategic planning and thus generate strategies for improvement and increase the terminal efficiency. Hypothesis The causes of the limitations such as the failure rate of professional level students in the economic-administrative areas at the Autonomous University of Sinaloa are related to the effects of the traditional methodology, where the evaluation process stands out without reconsidering the results and a teaching-learning process with limited student participation. It was found that there are several causal phenomena of failure at the higher level, highlighting among these aspects of student, teacher, and institutional responsibility, so it is recommended that the university authorities address these problems from the aspects related to quality control programmes, such as: accreditation programmes, teacher training, attention to dropout, among others.